Reclamation of Former Brick Mining Lands: Enhancing Oil Palm Growth Using Goat Manure and Rice Husk Charcoal - Maryani, Anis Tatik; Sarman, Sarman; Rosyani, Rosyani; Adri, Adri; Atman, Atman; Firdaus, Firdaus; Saidi, Busyra B; Wibowo, Yudha Gusti; Yardha, Yardha (Universitas Diponegoro, 2025)
This study focuses on the impact of goat manure and rice husk charcoal distribution on oil palm cultivation in former mining lands. The objective is to determine the optimal combination of goat manure and rice husk charcoal that enhances the growth of oil palm plants on these lands. Conducted in Pijoan Village, Muaro Jambi District, Jambi Province in 2021, the research utilized a completely randomized block design with 8 treatments and 3 repetitions, yielding 24 experimental units. The eight treatments consisted of varying ratios of goat manure to rice husk charcoal: (P1) 150 g goat manure + 325 g rice husk charcoal per planting hole, through (P8) 325 g goat manure + 150 g rice husk charcoal per planting hole. Results indicated that the combination of 325 g goat manure + 150 g rice husk charcoal (P8) provided the best outcomes in plant height, stem diameter, leaf balance at the third frond, and total frond count on reclaimed land.